Diretrizes para projetos de estabelecimentos de saúde militares com sistemas modulares volumétricos - Lopes, Lisiane de Souza Rodrigues (Universidade do Vale do Rio dos Sinos, 2024)
The theme of this research deals with the projects of military health care facilities using the Volumetric Modular System in the State of Rio Grande do Sul. A large number of military organizations are known in this territory, causing a large flow of people to medical and hospital care. Therefore, the need for advance planning of improvements or expansions of facilities is necessary to meet these demands, since traditional construction systems are slow. The research then raises the question of how it is possible, with the use of the Volumetric Modular System, to plan modules of parts of military health care facilities, obtaining flexibility and saving time in design and execution in this way. The general objective of the work was to define guidelines for design methodology for military health care facilities using volumetric modular prefabricated systems, thus improving the design process. Such guidelines are relevant to managers of Military Health Organizations, serving as support in making decisions quickly and assertively, thus providing advance planning of improvements in hospital facilities. The research is based on: a survey of the minimum requirements program for these organizations; studies on the Volumetric Modular System and its advantages; compositional solutions for healthcare facility buildings using this system; and trends and regulations on this topic. The method involved documentary and exploratory experiments on the compositions of what are the base modules and multi-modules of floor measurement, individually and in a compositional way, according to projects and demands of the hospital unit present in military hospitals, with the aim of constituting three-dimensional volumetric modules. The results showed that it is possible to use the volumetric modular system in the preparation of projects for military healthcare facilities using this methodology created based on the design guidelines for guidance purposes.
Keywords: Arquitetura hospitalar; Construção modular; Sistema modular volumétrico; Módulo; Projeto modular; Edifício modular; Hospital architecture; Modular construction; Volumetric modular system; Module; Modular design; Modular building; ACCNPQ::Ciências Sociais Aplicadas::Arquitetura e Urbanismo